Phytochemical screening of bioactive compounds and antioxidant activity of methanol extract from Melia Azedarach L. fruit: Exploring for antidiabetic potential - Qurratu Aini; Nurdin Nurdin; Mustanir Mustanir; Safrida Safrida; Tio R. Fauzi (Narra Sains Indonesia, 2025)
Melia azedarach L. (neem fruit) is a traditional plant with diverse bioactive constituents, yet its phytochemical profile and pharmacological potential remain underexplored. This study aimed to screen bioactive compounds and evaluate the antioxidant activity of methanol extract from M. azedarach fruit, while further performing computational exploration on its antidiabetic potential. M. azedarach fruits were macerated in methanol and analyzed through phytochemical screening, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity (DPPH assay). GC-MS was used to identify chemical constituents. Molecular docking was performed using a blind docking approach in CBDock2 against five protein targets, which included DPP-4, PTPN1, α-amylase, NrfA, and AKR1B1. Protocol validation was ensured by successful re-docking of co-crystallized ligands (RMSD < 2.0 Å). The extract was observed to contain terpenoids, steroids, flavonoids, and phenolics, with high TPC (479.8 mg GAE/g) and TFC (52.7 mg QE/g). Antioxidant activity was moderate (IC50 = 102.27 µg/mL). GC-MS identified 14 compounds, including cucurbitacins, ursolic acid derivatives, α-amyrin, taraxasterol, and ergostane-type sterols. Docking revealed moderate affinities (–5.0 to –6.5 kcal·mol-1) for most compounds. The cucurbitacin bound α-amylase (–13.6 kcal·mol-1) and NrfA (–8.5 kcal·mol-1), and taraxasterol exhibited broad-spectrum activity across all targets (–7.1 to –9.2 kcal·mol-1). M. azedarach fruit demonstrates moderate antioxidant activity and contains diverse phytochemicals with multitarget interactions relevant to glucose regulation. Strong binding to DPP-4, PTPN1, α-amylase, and AKR1B1 suggests potential antidiabetic properties through inhibition of carbohydrate digestion, enhancement of insulin signaling, and prevention of diabetic complications.